A Typha Angustifolia-Like MoS2/Carbon Nanofiber Composite for High Performance Li-S Batteries - Gu, Xingxing; Kang, Han; Shao, Chengbin; Ren, Xiaolei; Liu, Xiaoteng (Frontiers in Chemistry, 2020)
A Typha Angustifolia-like MoS2/carbon nanofiber composite as both a chemically trapping agent and redox conversion catalyst for lithium polysulfides has been successfully synthesized via a simple hydrothermal method. Cycling performance and coulombic efficiency have been improved significantly by applying the Typha Angustifolia-like MoS2/carbon nanofiber as the interlayer of a pure sulfur cathode, resulting in a capacity degradation of only 0.09% per cycle and a coulombic efficiency which can reach as high as 99%.